2014
DOI: 10.1016/j.jcmg.2014.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of Myocardial Magnetic Resonance Perfusion to Diagnose Ischemic Stenosis With Fractional Flow Reserve as Reference

Abstract: With FFR as the reference standard, the diagnostic ability of MR perfusion to detect ischemic CAD is high.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(55 citation statements)
references
References 52 publications
1
52
0
2
Order By: Relevance
“…A number of recent studies of perfusion CMR have used invasive FFR as a reference standard with good results. [9, 30] A meta-analysis by Jiang et al reports a sensitivity and specificity of 88% each when FFR is used as a reference standard. Future studies of the rapid ungated approach could possibly be better validated using FFR as the reference standard in all patients, even in patients without stenoses that appear significant by visual assessment.…”
Section: Discussionmentioning
confidence: 99%
“…A number of recent studies of perfusion CMR have used invasive FFR as a reference standard with good results. [9, 30] A meta-analysis by Jiang et al reports a sensitivity and specificity of 88% each when FFR is used as a reference standard. Future studies of the rapid ungated approach could possibly be better validated using FFR as the reference standard in all patients, even in patients without stenoses that appear significant by visual assessment.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, stress perfusion CMR can detect functionally significant CAD with excellent diagnostic accuracy. In a meta-analysis reported by Li et al [12], perfusion CMR allowed for the accurate detection of ischemic CAD with FFR as the reference standard. The pooled sensitivity, specificity, and AUC were 0.90, 0.87, and 0.95 at the patient level and 0.89, 0.86, and 0.93 at the vessel level, respectively.…”
Section: Cviamentioning
confidence: 99%
“…Stress perfusion CMR offers several advantages over SPECT, including a high spatial resolution and no radiation exposure. Stress perfusion CMR yields high diagnostic accuracy for the detection of CAD [3][4][5][6][7][8][9][10][11][12][13], and its prognostic value has also been documented [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Li et al showed that with FFR as the reference standard, the pooled sensitivity and specificity of stress perfusion CMR were 90% and 87%, respectively 10. They also demonstrated that CMR could increase the post-test probability of CAD to over 80% in patients with a pretest probability (PTP) of >37% and could decrease post-test probability of CAD to <20% with a PTP of <72%.…”
Section: Ischaemia Detectionmentioning
confidence: 99%